Community participation in managing secondary school academic performance: A case of selected secondary schools in Kilosa district council - Wanjara, Shukurani (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management (SOPAM) in partial fulfillment of the requirements for the award of the Degree of Master of Public Administration (MPA) of Mzumbe University.